2002
DOI: 10.1038/sj.leu.2402337
|View full text |Cite
|
Sign up to set email alerts
|

Ajoene, an experimental anti-leukemic drug: mechanism of cell death

Abstract: The organosulfur compound ajoene, a constitutent of garlic, has been shown to induce apoptosis in a leukemic cell line as well as in blood cells of a leukemic patient. The mechanisms of action of ajoene, however, are unknown. The present study aims to characterize the molecular events leading to ajoenetriggered apoptosis. We show here that ajoene (20 M) leads to a time-dependent activation of caspase-3-like activity as well as to the proteolytic processing of procaspase-3 and -8. Activation of caspases was nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 40 publications
4
43
0
Order By: Relevance
“…Therefore, we examined whether activation of JNK is a consequence of MMP or occurs independently of mitochondrial perturbation. Previous data have shown that cells overexpressing mitochondria-protecting Bcl-x L exhibit a significant reduced cell death rate in response to ajoene (Dirsch et al, 2002). In contrast, ajoene-induced activation of JNK is not altered by Bcl-x L overexpression ( Figure 2a).…”
Section: Ajoene-induced Jnk Activation Occurs Independently Of Mitochmentioning
confidence: 64%
See 4 more Smart Citations
“…Therefore, we examined whether activation of JNK is a consequence of MMP or occurs independently of mitochondrial perturbation. Previous data have shown that cells overexpressing mitochondria-protecting Bcl-x L exhibit a significant reduced cell death rate in response to ajoene (Dirsch et al, 2002). In contrast, ajoene-induced activation of JNK is not altered by Bcl-x L overexpression ( Figure 2a).…”
Section: Ajoene-induced Jnk Activation Occurs Independently Of Mitochmentioning
confidence: 64%
“…As mentioned before, ajoene induces the intrinsic pathway of apoptosis involving the induction of ROS upstream of mitochondria-dependent caspase activation (Dirsch et al, 2002). The aim of the present study was to clarify the participation of MAPKs and Akt in the apoptotic signaling of this organosulfur compound.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations